The Zoological Imagination of Early Christians: Review of Patricia Cox Miller, In the Eye of the Animal: Zoological Imagination in Ancient Christianity - Beverly, Jared (Humanimalia, 2020)
Patricia Cox Miller. In the Eye of the Animal: Zoological Imagination in Ancient Christianity. Divinations: Rereading Late Ancient Religion. Philadelphia: University of Pennsylvania Press, 2018. 280 pp. 79.95.